Orthogonal Decomposition in Omega-Weighted Classes of Functions Subharmonic in the Half-Plane (2018)
The paper gives a harmonic, ω-weighted, half-plane analog of W. Wirtinger's projection theorem and its (1 - r)α-weighted extension by M. Djrbashian and also an orthogonal decomposition for some classes of functions subharmonic in the half-plane.